Kinutye ofitsial'no - Sárosi, Péter; Takács, Gábor István (Hungary, 2010)
The number of people living with HIV/AIDS in Eastern Europe and Central Asia rose to 1.5 million in 2007, almost 69 percent live in the Russian Federation. According to UN estimations, more than 60 percent of new transmission are due to the sharing of injecting equipment. HIV prevention programs in Russia were all funded externally, by the Global Fund to Fight AIDS, Tubercolosis and Malaria. As Russia became a higher income country, it is no longer eligible for such support, but Russia refuses to keep funding these programs once the Global Fund support stops. This film was successfully used by Russian NGOs working in the HIV filed to ask the Global Fund for an extension of the support.
Verzio Film Festival Submission
Keywords: Documentary films